Journal Information and Editorial Board - Volume 5, Issue 1, 2020 - `Idealogy Journal, ` (Idealogy Journal; Vol 5 No 1 (2020): Idealogy Journal (April 2020)DO - 10.24191/idealogy.v5i1.286, 2021)
No abstract